PEMBELAJARAN AL-QUR’AN MELALUI METODE HALAQAH DAN KORELASINYA DENGAN TEORI BELAJAR SOSIAL ALBERT BANDURA DI MADRASAH AL-LAILIYYAH PPHM LIRBOYO - Ubaidillah; Ahnan Hasan Marullah; Zaqi Mubaraq (PT. Saha Kreasi Indonesia, 2025)
This study examines the implementation of the halaqah method in Qur’anic learning and its correlation with Albert Bandura’s Social Learning Theory. The research addresses how the halaqah model encourages students’ activeness and internalization of Qur’anic reading skills through observation, imitation, and social interaction. Using a qualitative descriptive approach conducted at Madrasah Al-Lailiyyah PPHM Lirboyo, data were obtained through direct observation of daily halaqah sessions held after Maghrib prayer. The study reveals that learning through halaqah fosters social motivation and discipline, supported by peer and teacher feedback as positive reinforcement. The reciprocal relationship among students, the environment, and behavior reflects Bandura’s concept of reciprocal determinism. The findings suggest that the halaqah method effectively integrates cognitive, social, and spiritual dimensions in Qur’anic education, forming a dynamic and continuous learning process.